MITIGATION A HARMFUL EFFECTS OF LIVESTOCK ON THE ENVIRONMENT IN UKRAINE - Labenko, Oleksandr (Economics of Agriculture, 2014)
The potential to reduce the sectors (livestock) emissions is large. Technologies practices that help reduce emissions exist but are not widely used. The adoption and use of best practices and technologies by the bulk of the worlds producers can result in significant reductions in emissions. The FAO report indicated that the emissions could be reduced by between 18 and 30 percent (or 1,8 to 1,1 gigatones CO2 – eq), if producers in a given system, region and climate adopted the practices currently applied by the 10 to 25 percent of producers with the lowest emission intensity. Most of the technologies and practices that mitigate emissions also improve productivity and can contribute to food security and poverty alleviation as the planet needs to feed a growing population. Under the conditions of the limited financial resources for the purpose of the implementation of government programs to minimize the harmful farm animal waste, such funds can be raised by participating in the emissions market.